Penerapan IoT dalam Monitoring dan Pengendalian Kualitas Air - Muhammad Yusri; Yani Maulita; Hermansyah Sembiring (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
The decline in water quality is a serious environmental issue, particularly in urban areas. This research aims to develop an Internet of Things (IoT)-based water quality monitoring system using ESP32, pH, TDS, and turbidity sensors. The system is designed to monitor water quality parameters in real-time and transmit data to a cloud platform for further analysis. The system prototype was tested with water samples from various sources, and the results demonstrated high accuracy, with a maximum deviation of ±0.5% compared to laboratory results. Thus, this system offers an efficient and easy-to-implement solution for continuous water quality monitoring, which can aid in water resource management in urban environments.